Repeating Marx: Introduction to the Special Issue “Karl Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory” - Christian Fuchs; Lara Monticelli (tripleC: Communication, Capitalism & Critique)
This introduction sets out the context of the special issue “Karl Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory”, which was published on the occasion of Marx’s bicentenary on 5 May 2018. First, we give a brief overview of contemporary capitalism’s development and its crises. Second, we argue that it is important to repeat Marx today. Third, we reflect on lessons learned from 200 years of struggles for alternatives to capitalism. Fourth, we give an overview of the contributions in this special issue. Taken together, the contributions in this special issue show that Marx’s theory and politics remain key inspirations for understanding exploitation and domination in 21st-century society and for struggles that aim to overcome these phenomena and establishing a just and fair society. We need to repeat Marx today.